Researching embodied relationships with place: rehabilitating the sit-down interview. (April 2020) - May, Vanessa; Lewis, Camilla
This article explores the utility of sit-down interviews in researching people's embodied relationships with place. We offer a critical intervention in the ongoing debates concerning methodological 'innovation' by exploring under which circumstances sit-down interviews can produce dynamic and embodied knowledge. We propose that when conducted in situ in an environment well known by both research participants and researchers, and when focused on inherently sensory topics, sit-down interviews can provide rich insights into embodied experiences of place. In addition, we contribute to the literature that compares sit-down interviews and walk-alongs by exploring the aspects of embodied experience that sit-down interviews might be more adept at capturing. Since there is considerable overlap in the kinds of knowledge that different interview methods can produce, we argue that it is impossible to divide social reality into distinct domains of experience, each with its own matching method of enquiry.